Translational Informatics Realizing the Promise of Knowledge-Driven Healthcare - Payne, Philip R.O; Embi, Peter J. (Health Informatics,, 2015)
Emergent and multidisciplinary research paradigms have fundamentally transformed biomedical science and the delivery of clinical care. A common theme spanning such transformative changes is the use of rigorous and systematic approaches to the collection, management, integration, analysis, and dissemination of data. Unfortunately, the absence of well-established theoretical and practical frameworks intended to address such needs remains a major impediment to the realization of a translational and knowledge-driven healthcare system. This book provides practical advice on the integrative and translational methodologies and frameworks that have transformed modern biomedical research Translational Informatics presents a broad framework and specific examples of how the deep integration of biomedical informatics with both biomedical research and clinical care delivery is essential to overcoming such barriers and achieving the benefits of a knowledge-based approach to the delivery of high-performance, quality, safe, and individually tailored healthcare. It will be of great value to a wide range of professionals involved in the discipline, as it: Defines the challenges and opportunities surrounding translational medicine, with a focus on the data, information, and knowledge needed to achieve such a healthcare model Introduces readers to core biomedical informatics theories and methods underlying the translational medicine paradigm Discusses future directions for the field of translational medicine.